The impact of heat stress in plant reproduction - Resentini, Francesca; Orozco-Arroyo, Gregorio; Cucinotta, Mara; Mendes, Marta A. (Frontiers in Plant Science, 2023)
The increment in global temperature reduces crop productivity, which in turn threatens food security. Currently, most of our food supply is produced by plants and the human population is estimated to reach 9 billion by 2050. Gaining insights into how plants navigate heat stress in their reproductive phase is essential for effectively overseeing the future of agricultural productivity. The reproductive success of numerous plant species can be jeopardized by just one exceptionally hot day.While the effects of heat stress on seedlings germination and root development have been extensively investigated, studies on reproduction are limited. The intricate processes of gamete development and fertilization unfold within a brief timeframe, largely concealed within the flower. Nonetheless, heat stress is known to have important effects on reproduction. Considering that heat stress typically affects both male and female reproductive structures concurrently, it remains crucial to identify cultivars with thermotolerance. In such cultivars, ovules and pollen can successfully undergo development despite the challenges posed by heat stress, enabling the completion of the fertilization process and resulting in a robust seed yield. Hereby, we review the current understanding of the molecular mechanisms underlying plant resistance to abiotic heat stress, focusing on the reproductive process in the model systems of Arabidopsis and Oryza sativa.